WOMEN ISSUES IN TWO SHORT STORIES BY RATNA INDRASWARI IBRAHIM: A STUDY OF COMPARATIVE LITERATURE TOWARD TWO SHORT STORY; ‘RAMBUTNYA JUMINTEN’ AND ‘BAJU’ - Putri Bestari Mardani; Devi Suprasti; Juni Aratika (Kajian Linguistik dan Sastra, 2017)
The  issue  of  women’s  life  has  always  been  an  interesting  topic  to  be discussed. This kind of issue has been widely delivered by story writers, which is by placing women as the main character in his/her work. It aims to convey the results of their thoughts in the form of literary works. As already been known, literary  works  are  one  of  an  essential  container  to  describe  the  reflexivity  of society.  Sensitive  issues  could  be  freely  expressed  in  literary  works.  As  an example  is  the  issue  of  women  which  is  described  in  short  stories  form  and published through the mass media. The  aims  of  this  paper  are  to  explain  the  forms  of  problems  or  issues revolving women that are presented in the ‘Baju’and ‘Rambutnya Juminten’text by Ratna Indraswari Ibrahim. This study uses the theory of feminism by Simone de Beauvoir. Beauvoir suggests that women are considered as the second-class citizens or as the second sex due to patriarchal power, a notion that can lead to gender inequality (Kuntowijoyo 1987: 136). Based on the study, it was found that both texts reveal various forms of women’s issues, which are patriarchy and gender constructions. Both traditional women and an empress with a high social position experience the same issue. Although the two female figures were trying to speak up, they are being ignored. This is because there is a widely known stereotype that states that women are emotional and irrational, so women are considered unable to manage their own lives and are not suitable to speak in a public sphere. Keyword:  comparative  literature,  feminism,  short  story,  Ratna  Indraswari, women issues.